PERLINDUNGAN HUKUM YANG BERKEADILAN BAGI PIHAK KETIGA PADA PERJANJIAN PERKAWINAN YANG BELUM DISAHKAN - Rina Dwi Kurnianingsih (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract For a valid marriage agreement and to be able to bind to a third party then the marriage agreement must be approved by the employee registration of marriage, this is in accordance with the provisions set forth in Article 29 paragraph (1). How juridical implications of the marriage covenant which is not authorized by the employee regarded the marriage registrar of civil aspect. What form of legal protection for third parties in a marriage that has not ratified the agreement. This paper aims to juridical implications and equitable form of legal protection for third parties in a marriage that has not ratified the agreement. This paper is based on normative legal research approach used is a statutory approach. The results of this study are the juridical implications of the agreement is not ratified marriage is still binding on the parties who made it and are not binding on third parties. Equitable form of legal protection for third parties in a marriage that has not ratified the agreement Being fair legal protection for third parties in a marriage that has not ratified the agreement is repressive legal protection is a third-party file a complaint or file a claim rights regarding unlawful act carried out by the husband and wife . Key words: law protection, equity, validation, marriage agreement Abstraksi Untuk sah perjanjian perkawinan dan agar dapat mengikat bagi pihak ketigaÂ maka perjanjian perkawinan tersebut harus disahkan oleh pegawai pencatatan perkawinan, hal ini sesuai dengan ketentuan yang diatur dalam Pasal 29 ayat (1). Bagaimana implikasi yuridis dari perjanjian perkawinan yang tidak disahkan oleh pegawai pencatat perkawinan dipandang dari aspek keperdataan. Bagaimana wujud perlindungan hukum bagi pihak ketiga dalam perjanjian perkawinan yang belum disahkan. Tulisan ini bertujuan untuk implikasi yuridis dan wujud perlindungan hukum yang berkeadilan bagi pihak ketiga pada perjanjian perkawinan yang belum disahkan. Tulisan ini berdasarkan Â penelitian hukum normatif pendekatan yang digunakan adalah pendekatan perundang-undangan. Hasil dari penelitian ini adalah implkasi yuridis dari perjanjian perkawinan yang tidak disahkan adalah tetap mengikat para pihak yang membuatnya dan tidak mengikat pada pihak ketiga. Wujud perlindungan hukum yang adil bagi pihak ketiga pada perjanjian perkawinan yang belum disahkan Wujud perlindungan hukum yang adil bagi pihak ketiga pada perjanjian perkawinan yang belum disahkan adalah perlindungan hukum represif yaitu pihak ketiga mengajukan keberatan atau mengajukan tuntutan hak mengenai perbuatan melawan hukum yang dilakukan pihak suami istri. Kata kunci: perlindungan hukum, keadilan, pengesahan, perjanjian perkawinan